PERAN ENTREPRENEURIAL COMMUNITY DAN DIGITAL ENTREPRENEURIAL ORIENTATION TERHADAP ENTREPRENEURAL PROCESS DALAM MENGHASILKAN ENTREPRENEURIAL PERFORMANCE - Nurjanah, Siti; Wahyudi, Triyono Arief (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This study aims to examine the role of the entrepreneurial community and digital entrepreneurial orientation towards the entrepreneurial process in producing entrepreneurial performance. Design/methodology/approach- The quantitative research design was used through field research in Wonogiri District, Baturetno District, Watuagung Village, Sendang Hamlet. A total of 31 respondents were randomly selected through questionnaires. Findings- The results of this study indicate that the entrepreneurial community does not affect the entrepreneurial process, digital entrepreneurial orientation influences the entrepreneurial process, entrepreneurial process influences entrepreneurial performance. Implication- Related parties need to make efforts to improve entrepreneurial performance through mentoring members of the community in directing and developing their businesses; conduct interactive communication between management and members of the association; and forming SME groups in the context of operational and development cost efficiency (production training, managerial finance, marketing, and others) Keywrods: entrepreneurial community, digital entrepreneurial orientation, entrepreneurial process, entrepreneurial performance